Perceptions of exclusive breastfeeding among Bidayuh mothers in Sarawak, Malaysia: a qualitative study - Chang, C.T; Denney, DF; Cheah, W.L (Nutrition Society of Malaysia, 2015)
Despite its benefits, exclusive breast feeding is not widely practised in Malaysia. As the decision for exclusive breastfeeding is influenced by social and cultural context, it is important to conduct studies in different societies in Malaysia. This qualitative study aimed to explore the perceptions of exclusive breastfeeding among Bidayuh women in Sarawak, Malaysia. Methods: A purposive sample of Bidayuh women who exclusively breastfed their infants for at least three months were recruited from one rural village in one sub-district of Kuching. An in-depth interview asked participants to respond to an open-ended questionnaire designed to elicit perception/challenges and motivating factors to continue exclusive breastfeeding. Results: Participants believed that it was their responsibility to breastfeed and breast milk was regarded as a gift from God with goodness that brought a proud and joyful experience. Breastfeeding also strengthened the mother-infant's physical and emotional bonding. Social support was important to ensure the continuation of exclusive breast feeding. Conclusion: Health care workers should emphasise these perceptions in their teaching and continue to provide support for exclusive breast feeding. More studies in other ethnic groups in Malaysia are recommended so as to provide relevant content for health care professionals to frame health education and promotion of exclusive breastfeeding within a culturally meaningful context.